Family’s Coping Strategies in the COVID-19 Pandemic: Systematic Literature Review - Annisa Puti Kusnadi; Hanny Mentari Putri; Edwin Rosario Riyantono; Ika Febrian Kristiana (Proceedings of International Conference on Psychological Studies (ICPSYCHE), 2022)
The COVID 19 pandemic has brought many changes to families and caused various problems related to mental health, especially stress. This study aims to see family’s coping strategies in dealing with the challenges of the COVID-19 situation. The method used is a systematic literature review using the 2015 PRISMA guideline. This study uses articles obtained from the Scopus, Proquest, ScienceDirect, and Springerlink databases. The article search method was carried out by entering the keywords "Coping Strategies" AND "Family" AND "COVID 19". The inclusion criteria for articles used are articles written in English, published in peer-reviewed journals, discussing coping strategies for families during the covid pandemic, using quantitative, mixed methods, and qualitative design, published between 2020-2021, and no cultural boundaries. There are 6 articles on coping strategies carried out by families during the COVID 19 situation met the inclusion research criteria. The results found that the coping strategies used by families during the pandemic were included in the problem focused form of coping mechanism, including sharing tasks between family members, managing time between work and family, and asking help from other groups. Coping strategies have a positive impact on problems experienced by families. Other parts outside the family have an important role in the family's coping strategy by providing social support. Future research can focus on coping strategies on certain conditions and cultures during the COVID 19 situation.